Typical course of cystinuria leading to untypical complications in pregnancy: A case report and review of literature - Ivandic, Ema; Maric, Marjan; Elvedi-Gasparovic, Vesna; Fistrek Prlic, Margareta; Lamot, Lovro; Jelakovic, Bojan; Vukovic Brinar, Ivana (Frontiers in Medicine, 2023)
Cystinuria is a rare genetic disorder which is characterized with excessive urinary excretion of cystine. This can lead to formation of cystine stones and development of chronic kidney disease. Symptoms usually start in the first two decades of life with typical presentation consisting of flank pain and renal colic, usually accompanied with urinary tract infection and deterioration of kidney function. Men are typically affected twice as often as women and have a more severe clinical course with more stone formation. Diagnosis is made by spectrophotometric analysis of the stones which are collected after spontaneous expulsion or medical intervention. Genetic testing is not mandatory but is recommended in uncertain cases or as a part of genetic counselling. Treatment consists of dietary intake recommendation, alkalization of urine and thiol-based therapies if other measures fail to prevent stone formation. Cystinuria with formation of cystine stones in pregnancy presents a challenge and requires a multidisciplinary approach consisted of uro-nephrology team and gynaecologist. We present a case of 38-year-old woman with cystinuria and manifested cystine stones during 3rd pregnancy with very complicated course and several urological interventions during pregnancy due to formation of new stones and worsening of kidney function. Despite all complications during pregnancy cared for by a multidisciplinary team, in the end she successfully delivered a healthy girl.